LOX-1 rewires glutamine ammonia metabolism to drive liver fibrosis - Huang, Ruihua; Cui, Hanyu; Yahya Ali Alshami, Mohammed Abdulaziz; Fu, Chuankui; Jiang, Wei; Cai, Mingyuan; Zhou, Shuhan; Zhu, Xiaoyun; Hu, Changping (Molecular metabolism (Germany), 2025)
Liver fibrosis is a crucial condition for evaluating the prognosis of chronic liver disease. Lectin-1ike oxidized low density lipoprotein receptor-1 (LOX-1) has been shown potential research value and therapeutic targeting possibilities in different fibrotic diseases. However, the role of LOX-1 and the underlying mechanisms in liver fibrosis progression remain unclear. LOX-1 expression was detected in liver tissues from patients and rodents with liver fibrosis. LOX-1 knockout rats were subjected to CCl4 or methionine and choline-deficient diet (MCD) to induce liver fibrosis. Transcriptomic and metabolomics analysis were used to investigate the involvement and mechanism of LOX-1 on liver fibrosis. We found that LOX-1 exacerbated liver fibrosis by promoting hepatic stellate cells (HSCs) activation. LOX-1 deletion reversed the development of liver fibrosis. We further verified that LOX-1 drove liver fibrosis by reprogramming glutamine metabolism through mediating isoform switching of glutaminase (GLS). Mechanistically, we revealed the crucial role of the LOX-1/OCT1/GLS1 axis in the pathogenesis of liver fibrosis. Moreover, LOX-1 rewired ammonia metabolism by regulating glutamine metabolism–urea cycle to drive the progression of liver fibrosis. Our findings uncover the pivotal role of LOX-1 in the progression of liver fibrosis, enrich the pathological significance of LOX-1 regulation of hepatic ammonia metabolism, and provide an insight into promising targets for the therapeutic strategy of liver fibrosis, demonstrating the potential clinical value of targeting LOX-1 in antifibrotic therapy. [Display omitted] •LOX-1 expression was significantly increased in the livers of liver fibrosis patients and animal models.•LOX-1 drove the progression of liver fibrosis by promoting the activation of hepatic stellate cells.•LOX-1 reprogrammed glutamine metabolism by mediating GLS isotype swift.•LOX-1 up-regulated GLS1 expression via enhancement of transcriptional regulation of OCT1.•LOX-1 rewired glutamine metabolism and urea cycle to disrupt ammonia homeostasis driving liver fibrosis.